ECONOMIC EVALUATION OF THE BUSINESS SCHEME FOR RKEF SMELTER DEVELOPMENT IN OPEN CAST NICKEL MINING OF PT XYZ USING THE REAL OPTION METHOD - Julia Fortuna, Fherin
Indonesia is a country with the world's largest nickel reserves. However, starting from January 1st 2020, regulations were established to prohibit the export of nickel ore in Indonesia, reguiring every nickel mining company to consider the processing and refining of nickel ore. In this study, an economic evaluation of the RKEF smelter development with a semi-finished product Nickel Pig Iron (NPI) was conducted. In this evaluation, the Real Option Analysis method was chosen as the economic evaluation approach because it can account for the value of flexibility options in long-term investment decision-making. The study was carried out by creating two business scenarios: mining without a smelter and mining with the development of a saprolite smelter. Both scenarios were then evaluated using the Discounted Cash Flow (DCF) method, and further tested using the Real Option Analysis method to obtain the best decision that could accommodate the volatility aspects of the investment being undertaken. Based on the calculation results using the DCF method, the NPV (Net Present Value) is $ 17,835,326.55 for scheme A and $ 111,191,637.04 for scheme B. The analysis was then followed by incremental analysis with an incremental IRR (Internal Rate of Return) of 29.4594. After the DCF analysis, option value calculations were performed using the binomial lattice approach. It was found that the best investment is the company with the RKEF smelter development, with an option value of $ 237,220,861.24 compared to the first seheme with an option value of $ 18,835,126.87.